CRISIS SITUATIONS IN URBAN PUBLIC TRANSPORT - Pavel Drdla; Josef Bulíček (Perner’s Contacts, 2012)
The paper is focused on characteristics of crisis situations in urban public transport. Individual crisis situations are divided by selected criterions and characterized in detail way. Field of crisis situations and its solution in the case of urban public transport in Prague is mentioned on the end on the paper.